Genome-Wide Analysis of BBX Gene Family in Three Medicago Species Provides Insights into Expression Patterns under Hormonal and Salt Stresses. - Wang J; Meng Z; He H; Du P; Dijkwel PP; Shi S; Li H; Xie Q (MDPI (Basel, Switzerland), 2024)
BBX protein is a class of zinc finger transcription factors that have B-box domains at the N-terminus, and some of these proteins contain a CCT domain at the C-terminus. It plays an important role in plant growth, development, and metabolism. However, the expression pattern of BBX genes in alfalfa under hormonal and salt stresses is still unclear. In this study, we identified a total of 125 BBX gene family members by the available Medicago reference genome in diploid alfalfa (Medicago sativa spp. Caerulea), a model plant (M. truncatula), and tetraploid alfalfa (M. sativa), and divided these members into five subfamilies. We found that the conserved motifs of BBXs of the same subfamily reveal similarities. We analyzed the collinearity relationship and duplication mode of these BBX genes and found that the expression pattern of BBX genes is specific in different tissues. Analysis of the available transcriptome data suggests that some members of the BBX gene family are involved in multiple abiotic stress responses, and the highly expressed genes are often clustered together. Furthermore, we identified different expression patterns of some BBX genes under salt, ethylene, salt and ethylene, salicylic acid, and salt and salicylic acid treatments, verified by qRT-PCR, and analyzed the subcellular localization of MsBBX2, MsBBX17, and MsBBX32 using transient expression in tobacco. The results showed that BBX genes were localized in the nucleus. This study systematically analyzed the BBX gene family in Medicago plants, which provides a basis for the study of BBX gene family tolerance to abiotic stresses.
Keywords: BBX; alfalfa; gene expression; stress response; transcription factors; Gene Expression Regulation, Plant; Plant Proteins; Salt Stress; Multigene Family; Phylogeny; Transcription Factors; Genome, Plant; Medicago sativa; Medicago; Plant Growth Regulators; Gene Expression Profiling; Genome-Wide Association Study; Stress, Physiological